ANALISIS ALTMAN Z-SCORE UNTUK MENILAI TINGKAT KESEHATAN KEUANGAN PERUSAHAAN MANUFAKTUR SUB SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2020 - Retno Sulati Sulaeman; Eka Nurcahyani (AKSELERASI: Jurnal Ilmiah Nasional, 2022)
This study aims to analyze the Altman Z-Score to assess the level of financial soundness of manufacturing companies in the pharmaceutical sub-sector. This research uses descriptive quantitative method. The type of data applied is quantitative data. Quantitative data in the form of business entity financial data obtained from annual financial reports that have been audited and published in pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2017 to 2020. Based on the results of the analysis, it can be seen that in 2017 and In 2018, there were five pharmaceutical companies that were in the healthy category and prone to bankruptcy. In the healthy category, namely PT Kalbe Farma Tbk, PT Industri Jamu and Pharmacy Sido Muncul Tbk, PT Tempo Scan Pacific Tbk, PT Darya-Varia Laboratoria Tbk, and PT Merck Tbk. Furthermore, there are four pharmaceutical companies that are in the category of prone to bankruptcy, namely, PT Kimia Farma Tbk, PT Indofarma Tbk, PT Phapros Tbk, and PT Pyridam Farma Tbk. Then for the category of bankrupt pharmaceutical companies in 2017 no one was in the bankruptcy zone. In 2019 there were two pharmaceutical companies that experienced a decline, namely, PT Kimia Farma Tbk which was previously in the bankruptcy prone category to be in the bankrupt category. And also happened to PT Merck Tbk, which was previously in the healthy category to be in the category of prone to bankruptcy. So that in 2019 there were pharmaceutical companies in the healthy category, four pharmaceutical companies in the bankrupt category, and one pharmaceutical company in the bankrupt category. In 2020 there were two pharmaceutical companies that experienced another decline, namely PT Darya-Varia Laboratoria Tbk which was previously in the healthy category into a bankruptcy-prone category, and PT Phapros Tbk which previously was in the bankruptcy-prone category into a bankrupt category. PT Kimia Farma Tbk remains in the bankrupt category. Meanwhile, PT Pyridam Farma Tbk experienced an increase from previously being in the category of prone to bankruptcy to being in the healthy category. So that in 2020 there are four pharmaceutical companies in the healthy category, three pharmaceutical companies in the bankruptcy prone category, two pharmaceutical companies in the bankrupt category.